Dynamic coordinated control during mode transition process for a compound power-split hybrid electric vehicle. (July 2018) - Su, Yanzhao; Hu, Minghui; Su, Ling; Qin, Datong; Zhang, Tong; Fu, Chunyun
Highlights: A plant model, including the engine and planetary dynamic model, is established. The shock and vibration problems during the mode transition process are investigated. A dynamic coordinated control strategy (DCCS) is proposed. The proposed DCCS can effectively improve the driving comfort. The proposed DCCS is also applicable to the engine shut-down process. Abstract: The fuel economy of the hybrid electric vehicles (HEVs) can be effectively improved by the mode transition (MT). However, for a power-split powertrain whose power-split transmission is directly connected to the engine, the engine ripple torque (ERT), inconsistent dynamic characteristics (IDC) of engine and motors, model estimation inaccuracies (MEI), system parameter uncertainties (SPU) can cause jerk and vibration of transmission system during the MT process, which will reduce the driving comfort and the life of the drive parts. To tackle these problems, a dynamic coordinated control strategy (DCCS), including a staged engine torque feedforward and feedback estimation (ETFBC) and an active damping feedback compensation (ADBC) based on drive shaft torque estimation (DSTE), is proposed. And the effectiveness of this strategy is verified using a plant model. Firstly, the powertrain plant model is established, and the MT process and problems are analyzed. Secondly, considering the characteristics of the engine torque estimation (ETE) model before and after engine ignition, a motor torque compensation control based on the staged ERT estimation is developed. Then, considering the MEI, SPU and the load change, an ADBC based on a real-time nonlinear reduced-order robust observer of the DSTE is designed. Finally, the simulation results show that the proposed DCCS can effectively improve the driving comfort.